Comparison of COD Determination Methods FAS Titrimetric with UV-Vis Spectrophotometry - Intan Wulandari; Uswatun Hasanah; Siti Warnasih (Helium: Journal of Science and Applied Chemistry, 2023)
Liquid waste is one of the factors causing contamination of the aquatic environment. One of the chemical parameters of water quality namely Chemical Oxygen Demand (COD). This research was conducted at three different concentration levels, namely low, medium, and high, with samples of river water, domestic wastewater, and sago liquid waste. The method used is UV-Vis spectrophotometry (SNI 6989.2: 2019) and FAS titrimetry (APHA, 2017 methods 5220 D); for the UV-Vis spectrophotometry method in the range 90 mg/L, the wavelength was measured at 420 nm, while for high levels in the range 100 mg/L x 900 mg/L, it was measured at 600 nm. The quality control parameters used are accuracy and precision parameters. The purpose of this study was to compare the COD determination between UV-vis spectrophotometry and FAS titrimetry and to determine the validity and correlation of the two methods—a comparison of the results of the two methods used in the F test. The results showed that the COD values from UV visible spectrophotometry and FAS titrimetry yielded good precision and accuracy values and met the acceptable limits, namely %RSD 10% and 90% accuracy %R 110%. However, the results of the COD analysis using the UV-Vis spectrophotometry method were lower by 0.8556 than the results of the COD analysis using the FAS titration method, with a correlation coefficient r2 = 0.982. The average concentration of UV-Vis spectrophotometry in samples of sago wastewater was 572.141 mg/L, domestic wastewater was 113.525 mg/L, and river water was 42.98 mg/L. The average COD level of the titrimetric method in sago wastewater was 641.888 mg/L, domestic wastewater was 219.251 mg/L, and river water was 58.016 mg/L. The results of the F test for these two methods produce an Fcount Ftable. The null hypothesis (Ho) is rejected, meaning there is a significant difference between the two methods.